2011
DOI: 10.1002/adma.201103463
|View full text |Cite
|
Sign up to set email alerts
|

Shrink‐Film Configurable Multiscale Wrinkles for Functional Alignment of Human Embryonic Stem Cells and their Cardiac Derivatives

Abstract: A biomimetic substrate for cell‐culture is fabricated by plasma treatment of a prestressed thermoplastic shrink film to create tunable multiscaled alignment “wrinkles”. Using this substrate, the functional alignment of human embryonic stem cell derived cardiomyocytes is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
96
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 33 publications
(45 reference statements)
5
96
0
Order By: Relevance
“…The surfaces created by these conventional fabrication processes are not representative of the underlying extra cellular matrix (ECM) fibrils in the native heart. We have previously demonstrated that a wrinkled substrate derived from plasma treated pre-stressed thermoplastic shrink film can potentially serve as an efficacious biomimetic surface to functionally align hPSC-CMs and prevent re-entry of ventricular arrhythmia [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surfaces created by these conventional fabrication processes are not representative of the underlying extra cellular matrix (ECM) fibrils in the native heart. We have previously demonstrated that a wrinkled substrate derived from plasma treated pre-stressed thermoplastic shrink film can potentially serve as an efficacious biomimetic surface to functionally align hPSC-CMs and prevent re-entry of ventricular arrhythmia [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological properties are often measured through the use of patch clamps [21] or fluorescent voltage sensitive dyes [19,20] which typically serve as end-point assays. With the prohibitive Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that hESCs aligned parallel to the wrinkled topography within hours of seeding when they were seeded onto polyethylene shrink films that included aligned wrinkles with depths that ranged from 150 to 300 nm. 70 Their nucleus became deformed and showed a decreased surface area. The cardiomyocytes differentiated from hESCs had contractions that were more synchronized than unaligned controls and the conduction velocity of the aligned cell action potentials was higher as well.…”
Section: The Effect Of Nanotopography Of a Substrate On Hpsc Lineage-mentioning
confidence: 99%
“…4 These approaches include techniques such as razor-blade cutting (xurography), 6,7 adhesive film masking, 8 and structuring through shape-memory polymers (SMPs), 9,10 among many others. Using these techniques, it has been possible to prototype microfluidic channels, [11][12][13] pattern thin films and surfaces, 8,14 and produce micro and nanostructured metallic surfaces [15][16][17] that have been applied mostly to Surface Enhanced Raman Scattering (SERS) applications. [18][19][20] The simplicity and cost-effectiveness of bench-top fabrication methods make them ideal for prototyping, optimizing, and producing low-cost disposable LoC devices.…”
Section: Introductionmentioning
confidence: 99%